FISH FARMING PRACTICES OF TRIPURA: A SOCIO-ECONOMIC PERSPECTIVE - SAHA, BISWARUP; PANDIT, ARUN (Journal of the Inland Fisheries Society of India, 2021)
This study was conducted to investigate the fish production practices in Tripura emphasising, input use and farmer’s perception. An expost facto research design was employed to collect data from 200 respondents randomly sampledfrom 10 villages. Instruments used for data collection included semi structured interview schedule, Participatory Rural Appraisal (PRA), researchers’ observations and secondary information. Descriptive statistics was used to report findings and to draw conclusions. The results showed that farmers adopted fish farming in order to obtain fish for household consumption and sale. The average fish yield was 1738 kg/ha. Fish culture contributed more than half of the total earning to 46% of the farmers. Majority of the fish farmers (20%) practiced the 5 species ratio of Rohu+Catla+Mrigal+Common Carp+ Silver Carp on the average ratio of 26.72 : 23.45 : 14.28 : 18.45 : 17.1. Yield was the most important criteria (96%) followed by availability of seed (85%) for species preference. Along with this, the extent of different inputs in fish production practices were also analysed. This finding suggested that farmer’s objectives and priority to be taken into account before introduction of technology and efforts should be directed towards realizing theobjectives.Key words: Fish production practice, inputs, perception, adoption, Tripuira